Antimony resistance mechanism in genetically different clinical isolates of Indian Kala-azar patients - Khanra, Supriya; Das, Shantanabha; Sarraf, Nibedeeta Rani; Datta, Sanchita; Das, Anjan Kumar; Manna, Madhumita; Roy, Syamal (Frontiers in Cellular and Infection Microbiology, 2022)
The central theme of this enterprise is to find common features, if any, displayed by genetically different antimony (Sb)-resistant viscerotropic Leishmania parasites to impart Sb resistance. In a limited number of clinical isolates (n = 3), we studied the breadth of variation in the following dimensions: (a) intracellular thiol content, (b) cell surface expression of glycan having N-acetyl-D-galactosaminyl residue as the terminal sugar, and (c) gene expression of thiol-synthesizing enzymes (CBS, MST, gamma-GCS, ODC, and TR), antimony-reducing enzymes (TDR and ACR2), and antimonial transporter genes (AQP1, MRPA, and PRP1). One of the isolates, T5, that was genotypically characterized as Leishmania tropica, caused Indian Kala-azar and was phenotypically Sb resistant (T5-LT-SSG-R), while the other two were Leishmania donovani, out of which one isolate, AG83, is antimony sensitive (AG83-LD-SSG-S) and the other isolate, T8, is Sb resistant (T8-LD-SSG-R). Our study showed that the Sb-resistant parasites, regardless of their genotype, showed significantly higher intracellular thiol compared with Sb-sensitive AG83-LD-SSG-S. Seemingly, T5-LT-SSG-R showed about 1.9-fold higher thiol content compared with T8-LD-SSG-R which essentially mirrored cell surface N-acetyl-D-galactosaminyl expression. Except TR, the expression of the remaining thiol-synthesizing genes was significantly higher in T8-LD-SSG-R and T5-LT-SSG-R than the sensitive one, and between the Sb-resistant parasites, the latter showed a significantly higher expression. Furthermore, the genes for Sb-reducing enzymes increased significantly in resistant parasites regardless of genotype compared with the sensitive one, and between two resistant parasites, there was hardly any difference in expression. Out of three antimony transporters, AQP1 was decreased with the concurrent increase in MRPA and PRP1 in resistant isolates when compared with the sensitive counterpart. Interestingly, no difference in expression of the above-mentioned transporters was noted between two Sb-resistant isolates. The enduring image that resonated from our study is that the genetically diverse Sb-resistant parasites showed enhanced thiol-synthesizing and antimony transporter gene expression than the sensitive counterpart to confer a resistant phenotype.